Comprehensive Radiation Dose Monitoring and Shielding Effectiveness Assessment in the Nuclear Medicine Hot Lab of INMAS, Pabna: Six Months Observation (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Radiation protection in nuclear medicine hot lab is essential to minimize occupational exposure during handling of radiopharmaceuticals. Continuous monitoring of dose rates and evaluation of shielding effectiveness are necessary to maintain safe working environments. Methods: A six-month observational study was conducted in the nuclear medicine hot lab at Institute of Nuclear Medicine and Allied Sciences (INMAS) Pabna. Monthly average dose rate measurements over six months and day-wise measurements during generator elution were recorded using a calibrated survey meter at 24-hour intervals across multiple locations including the fume hood (FH) surface, radial distances from the hood (0.15 m–1 m), inner and outer door surfaces of FH, post-dose handling area and corridor outside the hot lab. Dose attenuation and shielding effectiveness were analysed. Each location was selected to assess both high-risk zones and peripheral areas. Data were recorded in micro-Sieverts per hour (μSv/h). Results: The highest monthly mean dose rate was observed at the fume hood surface (37.85 ± 1.29 μSv/h), while the lowest value was recorded in the corridor (0.29 ± 0.01 μSv/h). Dose rate decreased progressively with increasing distance from the source and a strong negative correlation (r = -0.96) was observed between distance and dose rate. The shielding was corrected using a consistent half-value layer (HVL) approach for 99mTc gamma photons. Based on the measured fume hood surface dose rates, approximately 1.27 mm lead is required to reduce the monthly mean dose rate to 2.0 μSv/h and about 1.34 mm lead is required to reduce the peak elution dose rate to the same target. Conclusions: The results demonstrate effective radiation attenuation with distance and confirm that existing shielding and operational protocols maintain radiation exposure within acceptable safety limits. However, localized shielding enhancements near the fume hood may further improve radiation protection.Bangladesh J. Nuclear Med. 28(2): 257-262, July 2025